Influenza C infections in Western Australia and Victoria from 2008 to 2014. Issue 6 (23rd July 2016) - Jelley, Lauren; Levy, Avram; Deng, Yi‐Mo; Spirason, Natalie; Lang, Jurissa; Buettner, Iwona; Druce, Julian; Blyth, Chris; Effler, Paul; Smith, David; Barr, Ian G.
Abstract : Background: Influenza C is usually considered a minor cause of respiratory illness in humans with many infections being asymptomatic or clinically mild. Large outbreaks can occur periodically resulting in significant morbidity. Objectives: This study aimed at analyzing the available influenza C clinical samples from two widely separated states of Australia, collected over a 7‐year period and to compare them with influenza C viruses detected in other parts of the world in recent years. Patients/Methods: Between 2008 and 2014, 86 respiratory samples that were influenza C positive were collected from subjects with influenza‐like illness living in the states of Victoria and Western Australia. A battery of other respiratory viruses were also tested for in these influenza C‐positive samples. Virus isolation was attempted on all of these clinical samples, and gene sequencing was performed on all influenza C‐positive cultures. Results and conclusions: Detections of influenza C in respiratory samples were sporadic in most years studied, but higher rates of infection occurred in 2012 and 2014. Many of the patients with influenza C had coinfections with other respiratory pathogens. Phylogenetic analysis of the full‐length hemagglutinin–esterase–fusion (HE) gene found that most of the viruses grouped in the C/Sao Paulo/378/82 clade with the remainder grouping in the C/Kanagawa/1/76 clade.